POLYMERIC CLIP VERSUS ENDOLOOP FOR STUMP CLOSURE IN LAPAROSCOPIC APPENDICECTOMY-A RANDOMISED CONTROL TRIAL - MOHIT KUMAR BADGURJAR; AMIT KUMAR YADAV; SUMAN PARIHAR; SANJEEV KUMAR TUDU; NEHA BAPORIKAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives:: In laparoscopic appendicectomy, stump closure can be done by various methods such as endoloop, extracorporeal knots, intracorporeal ligatures, and gastrointestinal staplers. Polymeric clip was used in several studies in the closure of appendicular stump because of its lower cost and easy implementation. The purpose of this study is to investigate the safety, usefulness, and cost-effectiveness of polymeric clips versus endoloop in laparoscopic appendicectomy. Methods: We conducted a single blinded randomized controlled study on 100 patients of laparoscopic appendicectomy and divided them patients randomly into two groups (50 each) on the basis of technique used for stump closure (polymeric clip and endoloop). Results: On comparing the two matched groups we found there was a significant reduction in cost (35.36±3.29 vs. 39.56±3.12, respectively, *p<0.05) and operative time (909.00±63.64 vs. 1164.00±70.54, respectively, *p=0.05) in the group of polymeric clip as compared to endoloop. Although the post-operative complications and length of hospital stay were comparable in both the groups. Conclusion: Polymeric clip is not only a cost-effective option for patients but also a time-saving alternative for surgeons, while maintaining equally safe surgical outcomes when compared to endoloops.